Kontribusi Self-Efficacy Terhadap Kemampuan Penyesuaian Diri pada Mahasiswa Unnes Berkewarganegaraan Turki Tahun 2010 - Purnamasari, Lilis Ratna (Universitas Negeri Semarang, 2012)
Adjustment is one of the essential requirements for the creation of life and mental health of individuals. The new environment for some people is a stimulus occurrence of difficulties in adjusting. So is the case with Turkish students who experience anxiety when in a new environment (Indonesia) is very different from the country of origin. However, there are also some students who did not take a long time to get comfortable while in Indonesia. This study included in the quantitative correlational descriptive research. Instrument used in this study using psychological scales measuring tool. Validity test used in this study are product moment correlation and to test the reliability of the scales used psychology alpha formula. Analysis of non-parametric correlation data used is Spearman Rank. The results of calculation of correlation of 0.77, the results of these calculations indicate a positive correlation between the variables X with the variable Y. Thus, the hypothesis (Ha) that reads